Circulating tumor-reactive CD8+ T cells in melanoma patients contain a CD45RA+CCR7- effector subset exerting ex vivo tumor-specific cytolytic activity - Valmori, Danila; Schadendorf, Dirk (Cancer research, 2002)
To defend the host from malignancies, the immune system can spontaneouslyraise CD8+ T-cell responses against tumor antigens. Investigatingthe functional state of tumor-reactive cytolytic T cells in cancer patients is a key step for understanding the role of these cells in tumor immunosurveillance and for evaluating the potential of immunotherapeutic approaches of vaccination against cancer. In this study we identified a subset of circulating tumor-reactive CD8+ T lymphocytes, which specifically secreted IFN-γ after exposition to autologous tumor cell lines in stage IV metastatic melanoma patients. Additional phenotypic characterization using multicolor flow cytometry revealed that a significant fraction of these cells were CD45RA+CCR7−, a phenotype that has been proposed recently to characterize cytolytic effectors potentially able to home into inflamed tissues. In the case of an HLA-A2-expressing patient, the antigen specificity of this population was identified by using HLA-A2/peptide multimers incorporating a tyrosinase-derived peptide. Consistently with their phenotypic characteristics, A2/tyrosinase peptide multimer+ CD8+ T cells, isolated by cell sorting, were directly lytic ex vivo and able to specifically recognize tyrosinase-expressing tumor cells. Overall, these results provide the first evidence that a proportion of melanoma patients have circulating tumor-reactive T cells, which are lytic effectors cells.